Notary Responsibilities on Credit Agreement of Building Warranties Right (HGB) - Erny Herawati; Anis Mashdurohatun (Sultan Agung Notary Law Review, 2020)
The purpose of this study is conducted to: 1) Analyze the responsibility of the notary in the deed that is not in accordance with the provisions of paragraph of article 16 paragraph (1) item 1 and paragraph (7), Law office of a notary. 2) Analyze the responsibility of the notary in the manufacture of a credit agreement with a guarantee deed Building Warranties Right (HGB) maturing amid financing period. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed with descriptive methods analyst.